Strategi Pengembangan Kawasan Ekonomi Khusus (KEK) di Kota Bitung: Perspektif Sosial dan Ekonomi - Stanny Sicilia Rawung; Sharon Ribka Vivian Thealovely Kumendong; Merry Christie Natalia Rumagit; Vigilia Konda Montolalu (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study analyzes the role of SWOT analysis in improving the development of Special Economic Zones (SEZ) in Bitung City, conducted at the SEZ Administrator Office over three months. Primary data was collected through surveys, questionnaires, interviews, and documentation. In contrast, secondary data was obtained from relevant agencies such as the One-Stop Investment and Integrated Services Office (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu or DPMPTSP). The respondents consisted of 42 individuals. SWOT analysis revealed that the SEZ’s development strategy falls within the first quadrant, indicating a favorable alignment of external opportunities and internal strengths, with an Internal Factor Analysis Summary (IFAS) score of 3.48 and an External Factor Analysis Summary (EFAS) score of 3.72. Key strategies for SEZ development include utilizing fisheries and coconut resources to improve production and quality; enhancing infrastructure, including transportation and fishing ports, to support efficient distribution; improving human resource skills; fostering collective commitment among stakeholders, including the government, business actors, and the community; and building partnerships between local businesses and foreign investors to facilitate technology and capital transfer.